the Effect of Ability to Adjust Self, Work Achievement, and Work Satisfaction - Kartika, Savani; Prajanti, Sucihatiningsih Dian Wisika (Universitas Negeri Semarang, 2019)
The high quality of employee resources will result in strong commitment in completing routine tasks according to their respective responsibilities and functions more efficiently, effectively and productively. The extent of the authority possessed by the Province in the field of human resource management has resulted in the relevant agencies not carrying out their duties effectively. So that in this study research was conducted for; (1) analyze the ability of employees to adjust to colleagues; (2) analyzing employee work performance; (3) analyzing the level of employee job satisfaction and partial and simultaneous influence. The analytical tool used is Multiple Regression with classical assumption tests. The population in this study were 116 employees of Dispermadesdukcapil, Central Java Province, with a sample of 54 employees. The results of this study that variable adaptability and work performance have a significant positive effect, it is known from the tsatistic value of each of 4.458 and 3.853 which shows a number greater than the ttable number. While the variable job satisfaction has a positive and insignificant effect, it is known from the value of the statistic <t table of 1.698. If calculated together, the three variables have a significant positive effect known from the calculated f value> f-table by 58.548. The suggestions in this study need to be done to improve employees' work, or performance with difficulty behind education. Sumber daya karyawan yang berkualitas tinggi akan menghasilkan komitmen yang kuat dalam menyelesaikan tugas rutin sesuai dengan tanggungjawab dan fungsinya masing-masing secara lebih efisien, efektif dan produktif. Luasnya kewenangan yang dimiliki oleh Provinsi di bidang manajemen sumber daya manusia telah mengakibatkan instansi terkait tidak melaksanakan tugasnya secara efektif. Sehingga dalam penelitian ini dilakukan penelitian untuk; (1) menganalisis kemampuan karyawan untuk menyesuaikan diri dengan rekan kerja; (2) menganalisis kinerja karyawan; (3) menganalisis tingkat kepuasan kerja karyawan dan pengaruh parsial dan simultan. Alat analisis yang digunakan adalah Regresi Berganda dengan tes asumsi klasik. Populasi dalam penelitian ini adalah 116 karyawan Dispermadesdukcapil, Provinsi Jawa Tengah, dengan sampel 54 karyawan. Hasil penelitian ini bahwa variable kemampuan beradaptasi dan kinerja memiliki pengaruh positif yang signifikan, hal ini diketahui dari nilai t satistic masing – masing sebesar 4,458 dan 3,853 yang menunjukkan angka lebih besar dari angkat tabel. Sementara variable kepuasan kerja memiliki efek positif dan tidak signifikan, hal ini diketahui dari nilai statistic <t table sebesar 1,698. Jika dihitung bersama, ketiga variable tersebut memiliki efek positif signifikan yang diketahui dari nilai f hitung > f-tabel sebesar 58,548. Saran dalam penelitian ini perlu dilakukan untuk meningkatkan pekerjaan karyawan, atau kinerja dengan kesulitan di belakang pendidikan.